Effectiveness of Different Extraction Techniques on the Yield and Antityrosinase Activity of Merbau (Intsia bijuga (Colebr.) Kuntze) Wood Extract - Sari, Ratih Afrida Lismana; Sari, Rita Kartika; Safitri, Utami Dyah; Aristri, Manggar Arum; Wahyuningrum, Maeda; Lubis, Muhammad Adly Rahandi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
This study employed various extraction techniques to determine the yield, phytochemical profile, and antityrosinase activity of merbau wood (Intsia bijuga (Colebr.) Kuntze) extracts. The extraction techniques consisted of two factors: the type of extraction methods (conventional maceration – CM, ultrasound-assisted extraction – UAE, and magnetic stirrer – MS) and the number of extraction repetitions (first repetition – F1, second repetition – F2, and third repetition – F3). The interaction of the extraction methods and the number of extractions affects the extraction yield, antityrosinase activity, and its phytochemical profile. Merbau wood extracted using the UAE-F1 extraction method resulted in the highest yield (13.38%). In contrast, the UAE-F3 extract showed the strongest antityrosinase activity (IC50 value of 1.548 ppm) and the highest total phenol content (692.86 mg/g AGE). Fourier transform infrared analysis of the F1 extract showed that all samples contained the same functional groups, namely C=C (1600–1475 cm-1) and O-H (3800–3000 cm-1), indicating structural similarity among the extracts. Merbau wood extraction using the UAE method, both in the first, second, and third extractions, produced the highest yield, antityrosinase activity, and total phenol content of the extract compared to the CM and MS extraction methods. Keywords: antityrosinase activity, Intsia bijuga, maceration, total phenolic content, ultrasound-assisted extraction